Applications of IoT in Agricultural System - Ajit Kumar Singh (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Agriculture in India is the means of livelihood of almost two thirds of the work force in the country. It has always been India's most important economic sector. The increase in post independence agricultural production has been brought about by bringing additional area under cultivation, extension of irrigation facilities, use of better seeds, better techniques, water management and plant protection. The life of a farmer goes beyond tilling and yielding crops. The farmer should be alert to water the fields at regular intervals of time to obtain good results . To protect the field from drying due to lack of sufficient water and informing the owner of the field about the weather conditions in the field. To measure the different weather parameters in the field and soil moisture level in the field. It provides an easy and efficient technique to water the fields whenever the moisture level in the soil drops down. This system is entirely an automated one. The set up consists of ARDUINO UNO microcontroller, sensors as an important part as they are responsible for controlling the irrigation on field. ATMEGA 328P is an advanced version of microcontroller and forms the heart of the system. To measure different climate parameters, we are using different sensors like temperature, humidity sensors etc. To detect the rain fall and the humidity in the weather we are using the rain detect sensor and the humidity sensor respectively. All of the measured sensor parameters are sent to the predefined web server by using the Wi-Fi module. To this Wi-Fi module, we should provide the internet to that by using the mobile hot spot. And if any of the sensor activates, then the corresponding alert message will also send to the concerned person via SMS using the GSM module.